2011
DOI: 10.1029/2010ja015895
|View full text |Cite
|
Sign up to set email alerts
|

Planetary wave-tidal interactions over the equatorial mesosphere-lower thermosphere region and their possible implications for the equatorial electrojet

Abstract: [1] Optically measured daylight mean mesopause temperatures over a dip equatorial station, Trivandrum (8.5°N; 77°E; dip lat. 0.5°N), have been analyzed in conjunction with simultaneously measured equatorial electrojet (EEJ)-produced magnetic field at the surface. The signature of planetary wave-tidal interactions in the mesosphere-lower thermosphere (MLT) region has been observed for the first time in the day-to-day variability in the EEJ, i.e., the time of its peaking and the duration, as inferred from the EE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…A similar mechanism has been suggested to explain day‐to‐day variability in the temperature and wind fields in the mesosphere [ Anderson et al, ]. The influence of tides, gravity, and planetary waves propagating into the mesosphere, which have sources in the troposphere and stratosphere can contribute significantly to alter even the averaged characteristics of the EEJ [ Reddy and Devasia, ; Raghavarao and Anandarao, 1980 ; Somayajulu et al, ; Gurubaran, ; Abdu et al, ; Liu and Watanabe , ; Ramkumar et al ; Vineeth et al, , , ].The influence of local land‐sea and topographic contrasts has been pointed in theoretical work for the eastward propagating diurnal tide, results significant longitudinal variation in the local time EEJ variation [ England et al, ; Forbes et al, ]. However, detailed concurrent studies are required to correlate ionospheric observations with EEJ strength at closely spaced longitudes is yet to be carried out.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…A similar mechanism has been suggested to explain day‐to‐day variability in the temperature and wind fields in the mesosphere [ Anderson et al, ]. The influence of tides, gravity, and planetary waves propagating into the mesosphere, which have sources in the troposphere and stratosphere can contribute significantly to alter even the averaged characteristics of the EEJ [ Reddy and Devasia, ; Raghavarao and Anandarao, 1980 ; Somayajulu et al, ; Gurubaran, ; Abdu et al, ; Liu and Watanabe , ; Ramkumar et al ; Vineeth et al, , , ].The influence of local land‐sea and topographic contrasts has been pointed in theoretical work for the eastward propagating diurnal tide, results significant longitudinal variation in the local time EEJ variation [ England et al, ; Forbes et al, ]. However, detailed concurrent studies are required to correlate ionospheric observations with EEJ strength at closely spaced longitudes is yet to be carried out.…”
Section: Discussionmentioning
confidence: 80%
“…Several earlier studies sought explanations for these differences by correlating them with direct observations of ionospheric processes. Locally significant effects have been observed using optical airglow instrument, MF radar and found to correlate closely with the occurrence of CEJs at Trivandrum [ Ramkumar et al, ; Sridharan et al, ; Vineeth et al, , ], resulting the lowering of EEJ amplitude. The occurrence of CEJ results in the depression of the noontime EEJ by about 50% of its strength (Figure ) [ Somayajulu et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…The scatter in CEJ amplitude distribution is larger than the scatter of EEJ amplitude at 5° spatial separations (Figure and ), implying that CEJ is caused by shorter‐scale phenomena (~100, 1,000 km), where as the EEJ is driven by stronger effects, with large spatial scale length (Lühr et al, ). Experimental evidence of the short‐scale length perturbations were also obtained by direct measurements of wind and temperature in mesosphere (Abdu et al, ; Karan & Pallamraju, ; Tsuda, ; Vineeth et al, ).…”
Section: Discussionmentioning
confidence: 86%
“…Considerable observational evidence [ Fritts and Vincent , 1987; Teitelbaum et al , 1989; Manson et al , 1998; Pancheva , 2000, 2006; Pancheva et al , 2000; Haldoupis et al , 2004; Vineeth et al , 2011] has revealed that wave–wave interactions among tides, GWs, and PWs are ubiquitous in the mesosphere and lower thermosphere and play an important role in determining atmospheric structure and disturbances. Therefore such interactions have become subject of a great deal of theoretical interest [ Fritts and Vincent , 1987; Teitelbaum et al , 1989; Miyahara and Forbes , 1991; Liu and Hagan , 1998; Mayr et al , 1998; Smith and Ortland , 2001; Chang et al , 2011].…”
Section: Introductionmentioning
confidence: 99%